2018
DOI: 10.1002/jat.3612
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic cadmium exposure upregulates the mRNA level of genes associated to hepatic lipid metabolism in adult female CD1 mice

Abstract: Cadmium (Cd) is a persistent environmental and occupational contaminant that accumulates in humans and shows adverse effects on health. Accumulating evidence reveals that environmental Cd exposure is associated with hepatic lipid accumulation and metabolic alterations in adult male mice. However, whether Cd exposure induces hepatic lipid accumulation and metabolic alterations in female mice remains poorly understood. In the present study, we aimed to investigate the effects of Cd exposure on insulin resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 52 publications
(69 reference statements)
1
18
1
Order By: Relevance
“…The results were inconsistent with the study in which the subacute Cd exposure induced lipid accumulation in adult male mice(Go et al, 2015). There may be gender differences in the effects of Cd on the liver toxicity that has been discussed in our previous study(Zhang et al, 2018). However, the results were consistent with our previous study(Zhang et al, 2018), in which no significant lipid accumulation was observed after subchronic Cd exposure, although the mRNA level of genes associated to hepatic lipid metabolism was elevated in adult female mice.…”
contrasting
confidence: 96%
See 1 more Smart Citation
“…The results were inconsistent with the study in which the subacute Cd exposure induced lipid accumulation in adult male mice(Go et al, 2015). There may be gender differences in the effects of Cd on the liver toxicity that has been discussed in our previous study(Zhang et al, 2018). However, the results were consistent with our previous study(Zhang et al, 2018), in which no significant lipid accumulation was observed after subchronic Cd exposure, although the mRNA level of genes associated to hepatic lipid metabolism was elevated in adult female mice.…”
contrasting
confidence: 96%
“…There may be gender differences in the effects of Cd on the liver toxicity that has been discussed in our previous study(Zhang et al, 2018). However, the results were consistent with our previous study(Zhang et al, 2018), in which no significant lipid accumulation was observed after subchronic Cd exposure, although the mRNA level of genes associated to hepatic lipid metabolism was elevated in adult female mice. Mt, the metal-binding proteins and the most responsive proteins to Cd exposure, are small cysteine-…”
supporting
confidence: 92%
“…This element disrupts the adhesion of cells by displacement of Ca from E‐cadherin (transmembrane glycoproteins responsible for the proper adhesion of cells in a tissue) leading to activation of β‐catenins (signaling molecules) and an enhancement of cell proliferation (Bruscalupi, Massimi, Devirgiliis, & Leoni, ). Cd may affect gene expression and stimulate carcinogenesis by proto‐oncogene induction, inhibition of DNA methylation and disruption of cell signaling pathways (Chen et al, ; Fabbri et al, ; Tang et al, ; Zhang et al, ). It has been revealed in many experimental models that this element influences hepatocyte apoptosis and necrosis under conditions of in vivo and in vitro exposure (Chen et al, ; Mężyńska et al, ; Rogalska et al, ; Skipper et al, ).…”
Section: Mechanism Of CD Hepatotoxicitymentioning
confidence: 99%
“…an enhancement of cell proliferation (Bruscalupi, Massimi, Devirgiliis, & Leoni, 2009). Cd may affect gene expression and stimulate carcinogenesis by proto-oncogene induction, inhibition of DNA methylation and disruption of cell signaling pathways (Chen et al, 2014;Fabbri et al, 2012;Tang et al, 2013;Zhang et al, 2018). It has been revealed in many experimental models that this element influences hepatocyte apoptosis and necrosis under conditions of in vivo and in vitro exposure (Chen et al, 2014;Mężyńska et al, 2016;Rogalska et al, 2011;Skipper et al, 2016).…”
Section: Mechanism Of CD Hepatotoxicitymentioning
confidence: 99%
“…ions such as, zinc (Zn), copper (Cu), manganese (Mn) and iron bound to the enzymes and other biomolecules, interfere with the homeostasis of essential metals, trigger reactive oxygen species formation and disrupt the cellular function of biologically important molecules (Adiele, Stevens, & Kamunde, 2012;Kitamura & Hiramatsu, 2010;Zhang et al, 2018). Cells respond to Cd exposure with multi-strategies.…”
mentioning
confidence: 99%